A Contingent Resource-Based View of Proactive Corporate Environmental Strategy - Aragón-Correa, J. Alberto; Sharma, Sanjay (Academy of Management Review, 2003)
We integrate perspectives from the literature on contingency, dynamic capabilities, and the natural resource-based view of the firm to propose how dimensions of the general competitive environment of a business will influence the development of a dynamic, proactive corporate strategy for managing the business–natural environment interface. We also explain how certain characteristics of the general business environment—uncertainty, complexity, and munificence—moderate the relationship between the dynamic capability of a proactive environmental strategy and competitive advantage. We conclude with a discussion of implications for research and practice.